Analisis Tingkat Keramahtamahan Lingkungan Sekolah pada Sekolah Menengah Kejuruan - Intan Witari; Fadia Kalma Lailani; Rendyka Eliadi; Ernawati Ernawati; Rahmiati Rahmiati (Departement of Mathematics Education, 2023)
The purpose of this study was to analyze the level of prohibition in the school environment using the child-friendly school climate instrument based on the perceptions and experiences of students at Vocational High Schools in Ranah Pesisir District. The number of samples used in this study amounted to 170 people. Data collection was carried out by distributing questionnaires online using Google Forms to randomly selected students. Data analysis was carried out using descriptive analysis to see the environmental friendliness of the school and the level of environmental friendliness of the school. The results of the study showed that friendship among vocational schools in Ranah Pesisir District was in the high category. The friendliness of the school environment is described by four main dimensions, namely a safe environment for children, teacher support, individual social relations and a family atmosphere at school. However, there are still students who feel uncomfortable because of bullying and mistreatment and ridicule while at school.